Something Old and Something New—A Pilot Study of Shrinkage and Modern Imaging Devices - Hearing, Josephine V.W.; Horch, Raymund E.; Schmid, Rafael; Geppert, Carol-Immanuel; Stumpfe, Maximilian (Life, 2025)
Shrinkage, a heat-induced process, reorganizes collagen fibers, thereby reducing wound surface area. This technique, commonly applied in surgeries like periareolar mastopexy and skin grafting, is well-established. Despite its widespread use, modern imaging has recently enabled detailed observation of shrinkage’s effects on tissue temperature and oxygenation. The aim of this study is to investigate the effects of shrinkage on histological level, temperature, and tissue oxygenation. Skin flaps were collected, marked, and subjected to shrinkage in vitro, with wound dimensions recorded before and after shrinkage. Biopsy samples were analyzed histologically. In our clinical set up, Snapshot NIR® and FLIR thermography were used to assess tissue oxygenation and temperature changes before and after shrinkage. Shrinkage significantly reduced wound area by almost 47% ± 8.5%, with a 16.5% ± 6.0% reduction in length and a 36.5% ± 7.7% reduction in width. Tissue temperature rose by an average of 38.3 °C post-shrinkage, reaching approximately 65 °C. A slight decrease in oxygen saturation was observed following shrinkage. Histological analyses reveal collagen fiber denaturation and structural reorganization. Thermal shrinkage is an effective method for reducing wound size and tension, demonstrating potential for facilitating larger full-thickness skin grafts. Although minor decreases in oxygenation were observed, shrinkage may enhance wound healing by reducing tension at wound edges. Further studies are needed to quantify its impact on functional and cosmetic outcomes.
CRIS-Team Scopus Importer:2025-01-31
Keywords: collagen denaturation; shrinkage; temperature; tissue oxygenation; wound reduction